2005
DOI: 10.2166/ws.2005.0010
|View full text |Cite
|
Sign up to set email alerts
|

Municipal wastewater reclamation: where do we stand? An overview of treatment technology and management practice

Abstract: Water reclamation implementation and management practices at municipal wastewater treatment plants throughout the world are reviewed and some implementation and operational issues are defined. The information is based on a conventional literature survey, on an in depth survey study of European, Israeli and Australian medium and large-scale water reclamation utilities and on the findings of a dedicated international workshop. The review identified over 3,300 water reclamation projects and designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 9 publications
0
45
0
4
Order By: Relevance
“…The problem here is that the public is told that drinking water is the best controlled food in Germany, which is correct, but at the same time this fact may support the feeling that a change to using recycled water is unnecessary and that the unfamiliar system may have flaws. However, only a few people know that in many European urban areas, water cycles actually include the uncontrolled reuse of wastewater [15,30]. Information made available by waterworks and sewage plants to the public in Germany said that their tap water is perfectly clean of everything.…”
Section: Necessity Of Improvement For Wastewater Treatment Despite Nomentioning
confidence: 99%
See 2 more Smart Citations
“…The problem here is that the public is told that drinking water is the best controlled food in Germany, which is correct, but at the same time this fact may support the feeling that a change to using recycled water is unnecessary and that the unfamiliar system may have flaws. However, only a few people know that in many European urban areas, water cycles actually include the uncontrolled reuse of wastewater [15,30]. Information made available by waterworks and sewage plants to the public in Germany said that their tap water is perfectly clean of everything.…”
Section: Necessity Of Improvement For Wastewater Treatment Despite Nomentioning
confidence: 99%
“…Additionally, people wondered what had suddenly caused bacteria to appear in their drinking water, although nothing had happened to it, and only the information had been adapted (informal information from public outreach guide, BWB, Berlin). Bixio and colleagues [7,15] also concluded that the provision of new information may lead to lower acceptance from the public due to the high emotive load of the topic.…”
Section: Necessity Of Improvement For Wastewater Treatment Despite Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The use of reclaimed water has been already reported some decades ago and nowadays it represents a promising expanding market [6]. However, most of this reclaimed water is still used in agricultural and urban applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of this reclaimed water is still used in agricultural and urban applications [6]. In fact, only a low percentage of the total reclaimed water is nowadays used for industrial purposes, where it is mainly (> 50%) used as cooling water [7].…”
Section: Introductionmentioning
confidence: 99%